Optimizing Arabic Listening Skills: A Systematic Review and the Proposal of an Integrated Suggestopedic Brain-Based Learning (ISBBL) Model - Ridha, Muhammad Rasyid; M. Asdi Nurkholis; Khoirin Nikmah; Alin Safaraz Himam; Banna Irfan Ibadillah; Ahmad Mudzakkir Hamzah (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2025)
Proficiency in Arabic listening skills is often hindered by significant psychological barriers, such as foreign language anxiety. This study aims to address this challenge by developing a coherent pedagogical framework that integrates the affective strategies of Georgi Lozanov's Suggestopedia with the neuroscientific principles of Brain-Based Learning (BBL). A Systematic Literature Review (SLR) was conducted following PRISMA guidelines. The process began with the identification of 205 records from academic databases, which were then screened to yield a final corpus of 36 core articles for thematic synthesis. This synthesis focused on literature pertaining to Suggestopedia, Brain-Based Learning (BBL), and listening acquisition. The analysis revealed profound synergies between Suggestopedia's techniques (e.g., concert sessions) and BBL's core principles (e.g., relaxed alertness, emotional engagement). This synthesis resulted in the formulation of the Integrated Suggestopedic Brain-Based Learning (ISBBL) model—a novel, five-phase conceptual framework proposed to systematically guide learners from high anxiety to a state of relaxed, active engagement. The ISBBL model offers a practical framework for educators. While it awaits empirical validation, the model conceptually grounds the intuitive methods of Suggestopedia in the principles of educational neuroscience. This framework presents a structured approach to overcoming affective barriers in Arabic listening instruction and is recommended for further empirical research to validate its classroom efficacy.